2018
DOI: 10.14735/amko2018264
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Bioinformatics and Literature Based Approach for Identification of Long Non-coding RNAs That Modulate Vitamin D Receptor Signaling in Breast Cancer

Abstract: Kombinovaný bio informatický a literární přístup k identifikaci dlouhých nekódujících molekul RNA, které modulují signalizaci přes receptor vitaminu D u karcinomu prsu Kholghi Oskooei V., Ghafouri-Fard S., Omrani MD Department of Medical Genetics, Shahid Beheshti University of Medical Sciences, Tehran, Iran SummaryBackground: Long non-cod ing RNAs (lncRNAs) as an important fraction of human transcriptome have been shown to exert fundamental role in regulation of signal ing pathways implicated in carcinogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Some of these lncRNAs exert their effect in breast cancer through their interaction with microRNAs [99,100]. Some lncRNAs may regulate vitamin D metabolism and 1,25(OH)2D controls the expression of some miRNAs, which, in turn, regulate the mRNAs of genes involved in breast carcinogenesis [101][102][103].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Some of these lncRNAs exert their effect in breast cancer through their interaction with microRNAs [99,100]. Some lncRNAs may regulate vitamin D metabolism and 1,25(OH)2D controls the expression of some miRNAs, which, in turn, regulate the mRNAs of genes involved in breast carcinogenesis [101][102][103].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Previous reports demonstrated that 1a,25(OH) 2 D 3 could regulate some protein-coding genes (31)(32)(33). Three studies showed that VDR regulated lncRNA profiling in skin and breast cancer (24)(25)(26). However, to date, there was no study investigating whether 1a,25(OH) 2 D 3 could affect the expression pattern of lncRNAs in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that 1a,25(OH) 2 D 3 may play an important role in the control of cancer by mediating protein-coding genes. In addition, one and two reports studied vitamin D receptor (VDR)-regulated lncRNAs profiling in skin cancer and breast cancer, respectively (24)(25)(26). However, it is not clear which lncRNAs are regulated by 1a,25(OH) 2 D 3 in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, certain polymorphisms in the VDR gene have been linked to an elevated risk of several autoimmune diseases, including MS (2,4). More recently, it has been found that the expression of the VDR gene is infl uenced by a number of long noncoding RNAs (lncRNAs) (5).…”
Section: Introductionmentioning
confidence: 99%